Molecular phylogeny by Bayesian analysis and description of a new species of Henneguya, a parasitic cnidarian from Astyanax bimaculatus (Linnaeus, 1758) (Characiformes: Acestrorhamphidae) in Caatinga: A biome with neglected biodiversity data - Jorge, Maurício [UNESP]; Mathews, Patrick Delgado [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; Silva, Reinaldo José da [UNESP] (Elsevier, 2025)
Myxozoans are cnidarian parasites with a worldwide distribution and represent some of the most spectacular examples of parasite radiation. Based on an integrative taxonomic approach that includes spore morphology and molecular data, as well as other phenotypic characters such as host specificity, a new myxozoan, Henneguya caraubensis n. sp., is described from the gills of Astyanax bimaculatus (Linnaeus, 1758). Plasmodia were located within the gill lamellar epithelium, without connective tissue surrounding them. Mature myxospores were ellipsoidal in the frontal view, measuring 27.2 ± 2.6 μm in total length, 10.3 ± 0.7 μm in body length of spore, and 3.9 ± 0.2 μm in width. Two polar capsules elongated pyriform in shape, equal in size, measuring 3.4 ± 0.3 μm in length and 1.2 ± 0.1 μm in width. Polar tubules had 5 to 6 coils. Histopathological analysis showed large intralamellar polysporic plasmodia associated with displacement, deformation, and fusion of the nearest gill lamellae and with the adjacent lamellae being pushed laterally. Bayesian inference SSU rDNA-based phylogenetic analyses showed a strong tendency of Henneguya/Myxobolus species to form clusters mainly based on the order and/or family of the host, despite having different geographic origins. Phylogenetically, the novel species grouped within a clade containing Henneguya/Myxobolus spp. and appears in a well-supported subclade of Henneguya species parasites of Astyanax fishes. Our study reinforces highly endemic diversity still hidden that inhabits the Caatinga biome and points out the need to improve the strategies of protection and conservation of this threatened ecoregion with neglected biodiversity data.
Keywords: Biodiversity; Gill disease; Henneguya; Histopathology; Myxozoa; Neotropical region